Analysis of Surface Acoustic Wave Propagation Velocity in Biological Function-Oriented Odor Sensor. (13th March 2018) - Yang, Yuxia; Nagano, Koji; , Chaoluomeng; Iwasa, Tatsuo; Fukuda, Hisashi
Abstract : We describe the measurement of surface acoustic wave (SAW) velocities to identify five odorant molecules by using a SAW device system. We derive a new frequency equation for SAWs propagating in the SAW device system with Cynops pyrrhogaster lipocalin (Cp-Lip1) protein, in order to identify five odorant molecules, R-limonene (R-Lim), ethyl butyrate (Eth), 2-isobutylthiazole (Iso), benzophenone (Ben), and 2-acetylthiazole (Ace). We developed a method to identify these odorant molecules combined with the Cp-Lip1 odorant-binding protein. Our frequency equation can satisfactorily predict different odorant molecules in the Cp-Lip1 SAW device. Moreover, our data suggest that the propagation velocity of the SAWs mostly relate to the density and concentration of the Cp-Lip1 odorant molecule mixtures. At the same sample concentration, the propagation velocity depends on the density. For the same odorant molecule, the propagation velocity decreases with increasing concentration.